Characteristics of metastatic lung cancer patients on osimertinib therapy in Bangladesh - Arifur Rahman, M.; Yasmin, Taohida; Sharmin, Sadia; Chowdhury, Arman Reza; Mohsin Howlader, M.; Rokonuzzaman, S. M.; Zabin, Meher; Tania, Kamrun Nahar; Das, Arunangshu (International Journal of Research in Medical Sciences, 2025)
Background: Lung cancer is a major cause of mortality worldwide and metastasis plays a vital role in determining treatment and survival rate. Osimertinib showed significant success in the treatment of lung cancer, as evidenced by the literature, however, this outcome varies according to age, site of metastasis, etc. The objective of this study was to obtain demographic information on patients and assess the frequency of metastatic sites based on their age and sex. Methods: This descriptive cross-sectional study included eighty metastatic lung cancer patients on osimertinib therapy attending a tertiary level health facility in Dhaka, Bangladesh. Data were obtained through reviewing their clinical reports. Results: According to the findings, the patients’ mean (±SD) age was 60.95 ±13.98 years. Patients who were between the ages of 55 and 75 had the highest rate of metastases. Under the age of 55, brain metastases (27%) were more common in both sexes (16.2%). While spinal metastasis was more frequent in female patients (8.1%), skin metastasis was more common in male patients (16.2%). Skin metastases were most frequently observed in patients aged 55 to 65 (10.8%), followed by those aged 25 to 45 (5.4%). Conclusions: Mid-age male patients have been observed to have more cases of brain metastases and metastatic lung cancer. The findings are not conclusive due to the small sample size but suggest that the site of metastasis varied according to the patient’s demographic characteristics. Further research on this topic is recommended to yield evidence for practitioners and policymakers.